ECONOMIC ANALYSIS OF ECONOMIC INDICATORS AS A TOOL OF TAX REGULATION IN THE EURASIAN ECONOMIC UNION - E. Kirova (Publishing House of the State University of Management, 2017)
In article the economic analysis of indicators of development of economy of member countries of EEU is carried out, the reasons containing growth of innovative economy are established. The author draws a conclusion about unevenness of involvement of members of EEU in innovative process. It is offered to include questions of tax regulation in the sphere of uniform policy of member states of EEU.